Fast start-up of the cold-anammox process with different inoculums at low temperature (13 °C) in innovative reactor. (November 2018) - Wu, Peng; Chen, Ya; Ji, Xiaoming; Liu, Wenru; Lv, Gang; Shen, Yaoliang; Zhou, Qi
Graphical abstract: Highlights: Fast start-up of anammox process treating domestic sewage at low temperature (13 °C) was achieved. The microbial communities of three enriched reactors are similar. The enriched anammox species were different in the three reactors. The Ca . Brocadia sinica confirmed the fast anammox start-up. The hydraulic flow of the CAMBR insures the accumulation of anammox bacteria. Abstract: Three innovative reactors (CAMBR) through optimally combining with the Anaerobic Baffled reactor and Membrane bioreactor were applied to start up the cold-anammox process at low temperature (13 °C) through inoculating flocculent nitrification sludge (R1), anaerobic granular sludge (R2) and flocculent denitrification sludge (R3), respectively. Results showed that anammox process was started successfully with over 90% total nitrogen removal rate in R1, R2 and R3 after 75d, 45d, and 90d, respectively. Microbial community revealed that Ca . Brocadia and Ca . Jettenia were the dominant anammox bacteria in R1, R2 and R3, accounting for an abundance of 0.08%, 12.18%; 3.17%, 0 and 0.08%, 0.38%, respectively. Three anammox species, Ca . Brocadia caroliniensis, Ca . Brocadia sinica and Ca . Jettenia asiatica were annotated based on the phylogenetic tree, suggesting the anammox species with larger maximum growth rate contributed to the rapid start-up of the cold-anammox process. This study reinforces the potential application of mainstream anammox.